2014
DOI: 10.1186/1756-0500-7-457
|View full text |Cite
|
Sign up to set email alerts
|

Human plasma enhances the expression of Staphylococcal microbial surface components recognizing adhesive matrix molecules promoting biofilm formation and increases antimicrobial tolerance In Vitro

Abstract: BackgroundMicrobial biofilms have been associated with the development of chronic human infections and represent a clinical challenge given their increased antimicrobial tolerance. Staphylococcus aureus is a major human pathogen causing a diverse range of diseases, of which biofilms are often involved. Staphylococcal attachment and the formation of biofilms have been shown to be facilitated by host factors that accumulate on surfaces. To better understand how host factors enhance staphylococcal biofilm formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 34 publications
6
72
0
1
Order By: Relevance
“…First, the in vitro model used for biofilm development and susceptibility testing cannot adequately recapitulate biofilms developed in vivo, in which host factors absent under Table 1. Activity of Rifamycin Derivatives on Biofilms in vitro culture conditions could influence the biofilm phenotype and possibly affect antimicrobial activities observed herein [10]. However, the biofilm model used in this study is well characterized and has been demonstrated to be a reliable, reproducible experimental tool for evaluating susceptibilities of bacterial biofilms to various agents [3,11,13].…”
Section: Discussionmentioning
confidence: 99%
“…First, the in vitro model used for biofilm development and susceptibility testing cannot adequately recapitulate biofilms developed in vivo, in which host factors absent under Table 1. Activity of Rifamycin Derivatives on Biofilms in vitro culture conditions could influence the biofilm phenotype and possibly affect antimicrobial activities observed herein [10]. However, the biofilm model used in this study is well characterized and has been demonstrated to be a reliable, reproducible experimental tool for evaluating susceptibilities of bacterial biofilms to various agents [3,11,13].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, biofilms were grown as described above using glass chamber slides, as previously described (Cardile et al 2014). Following overnight treatment (inhibition or dispersal), biofilms were gently washed with sterile PBS, fixed for 10 min at room temperature with 4% paraformaldehyde in PBS, and stained using Film Tracer™ SYPRO ® Ruby Biofilm Matrix Stain, according to the manufacturer's instructions (Molecular Probes, Eugene, OR).…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the effect of norspermidine on the expression of genes related to homoserine lactone synthesis (A1S_0109 - A1S_0114) in A. baumannii , including a reference strain ATCC 17978 as well as three representative clinical isolates, biofilms were formed in 6-well tissue culture plates using previously described methods in the presence of 5 and 20 mM norspermidine (in 100mM HEPES) for 24 h at 37°C (Cardile et al 2014; Malachowa et al 2011). Following overnight incubation, supernatants were removed, individual wells were gently washed with PBS and attached bacteria (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The Staphylococcal MSCRAMMs are the Clf-Sdr family proteins, including Bbp (bone sialoprotein-bnding protein), the FnBPs (fibronectin-binding proteins), and CNA (collagen adhesion). Exposure of S. aureus to human plasma in vitro enhances both MSCRAMM expression and biofilm formation, suggesting the importance of their role in in vivo biofilm infections (43). …”
Section: Staphylococcal Adhesinsmentioning
confidence: 99%